Turkish kinship terms and classification characteristics - Шaдкaм, З. (Journal of Oriental Studies, 2017)
In the era of globalization, when seen weakening of the national values, it is necessary to explore kinship titles, which are playing an important role in maintaining and preserving the family and kinship ties in dint of contemporary and new methods as a part of cultural linguistics, ethno linguistics, psycholinguistics and culture sciences. In this article we will consider the classification of Turkish kinship titles, and also loanwords from Western languages and their wide application in society. Thus, we attempt to determine the features of the use of these concepts in the language and intercultural aspect, which are the manifestation of spiritual culture and cognitive experience of the people.